Interprofessional Medication Self-Management Program for Older Underserved Adults - Kim, Jennifer (Patient Prefer Adherence, 2020)
INTRODUCTION: Older adults have complex medication self-management challenges that can contribute to poor disease control. METHODS: In 2016, an interprofessional medication self-management program was implemented in an internal medicine primary care residency clinic caring for a large proportion of indigent patients. This was a 1-year, quasi-experimental, pre–post study approved by the Institutional Review Board to evaluate the impact of this program on hypertension and diabetes control in older adults. Patients aged 60 years or older with both systolic blood pressure > 140 mm Hg and A1C > 7.5% were included in the study; patients who did not have these characteristics were excluded. Interprofessional team members (nurses, certified medical assistants, pharmacist, dietician, social worker, and nurse technician) obtained 6-month medication fill histories from pharmacies and provided findings to physicians prior to patient appointments. During patient appointments, medication self-management interventions were performed such as motivational interviewing and regimen simplification. Members contacted patients by phone after each appointment for ongoing medication self-management support. RESULTS: Of 50 patients, the mean age was 67 years, 78% were female, 88% were black, the mean baseline systolic blood pressure was 159.8 mm Hg, and A1C was 9.7%. The 1-year mean systolic blood pressure was significantly reduced [151.5 mm Hg vs 141.8 mm Hg, −9.7 mm Hg difference, 95% confidence interval (CI) −6.19 to −13.19, P < 0.001], and the 1-year mean A1C was significantly reduced (9.6% vs 8.6%, −1.0% difference, 95% CI −0.49 to −1.39, P < 0.001) after implementation. Compared to baseline, the mean systolic blood pressure and A1C were significantly lower at each follow-up visit. CONCLUSION: This interprofessional medication self-management initiative improved systolic blood pressure and A1C in underserved older adults in an internal medicine residency clinic.